2015
DOI: 10.1158/1055-9965.epi-15-0401
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the AYA HOPE Comorbidity Index on Assessing Health Care Service Needs and Health Status among Adolescents and Young Adults with Cancer

Abstract: Background Existing comorbidity indices were not developed for adolescent and young adults (AYA) 15–39 years of age. The aim of this study was to assess impact of comorbidities on healthcare service needs and health status among AYA cancer survivors using the newly developed AYA HOPE comorbidity index in comparison with the existing indices. Methods Data on comorbid conditions were obtained from medical records and service needs and health status were from a survey of AYA cancer survivors. Prevalence of como… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
(43 reference statements)
1
13
0
1
Order By: Relevance
“…Unmarried patients reported worse mental health. Other areas that influenced HRQOL outcomes included comorbidities (for which an index tailored to this age group was developed), unmet service needs, and negative perceptions of control over their lives . Overall, our findings suggest that subgroups of AYA patients with cancer experience major decrements in several physical and mental HRQOL domains.…”
Section: Impact Of Cancer On Social Psychological and Functional Oumentioning
confidence: 75%
See 1 more Smart Citation
“…Unmarried patients reported worse mental health. Other areas that influenced HRQOL outcomes included comorbidities (for which an index tailored to this age group was developed), unmet service needs, and negative perceptions of control over their lives . Overall, our findings suggest that subgroups of AYA patients with cancer experience major decrements in several physical and mental HRQOL domains.…”
Section: Impact Of Cancer On Social Psychological and Functional Oumentioning
confidence: 75%
“…Recent European research has also shown a dearth of available AYA‐focused supportive care . In AYA HOPE, factors associated with unmet services included having two or more comorbidities and reporting any physical symptoms . Unmet service needs were also associated with worse mental, physical, and overall HRQOL .…”
Section: Care Experiences and Unmet Needsmentioning
confidence: 99%
“…AYA patients often receive fragmented care as they are caught between pediatric and adult oncology, perhaps increasing the likelihood of polypharmacy and multiple prescribing physicians. Compared with older cancer survivors, AYA cancers survivors have earlier onset chronic conditions that accumulate over the life course . Many AYA survivors report unmet health care needs, particularly for the late effects of treatment, mental health, weight management, and pain management .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with older cancer survivors, AYA cancers survivors have earlier onset chronic conditions that accumulate over the life course . Many AYA survivors report unmet health care needs, particularly for the late effects of treatment, mental health, weight management, and pain management . Financial challenges also may compromise adherence to multiple prescription regimens .…”
Section: Discussionmentioning
confidence: 99%
“…Zum einen ist die durchschnittliche Prognose bei Krebs in diesem Alter überdurchschnittlich gut, andererseits bleiben AYA-Krebs-Patienten im Unterschied zu älteren Erwachsenen noch auf Jahrzehnte mit den weitreichenden Folgen der Krebsdiagnose und -behandlung konfrontiert (3)(4)(5)(6)(7)(8)(9)(10). Diese lebenslange Erfahrung wird als ein kontrastreiches Lebensgefühl, weil grundsätzlich verschieden und mit einer erhöhten Vulnerabilität für körperliche und psychosoziale Spätkomplikationen behaftet, im Vergleich zu dem Lebensgefühl der "gesunden" Gleichaltrigen empfunden (11)(12)(13)(14)(15). "Ich bin jetzt 28, habe ein Kind und eine eigene Familie.…”
unclassified